EXAMINING THE WITHIN-PERSON COUPLING OF CONTROL BELIEFS AND COGNITION IN OLDER ADULTS - Zhang, S. (Innov Aging, 2017)
The current study examined the within-person relationship (e.g., coupling) between control beliefs and cognition in a heterogeneous sample of older adults and whether race moderated this relationship. The sample consisted of 206 community-dwelling elders ranging in age from 60 to 94 (M = 73, SD = 7.00), of which 22 were African American (AA). Participants completed a computerized cognitive battery and Daily Control Belief Questionnaire over eight testing occasions over a 2–3 week period. Daily Control Belief Questionnaire included two subscales: locus-of-control scale (higher scores reflected more internal control) and perceived competence scale (higher scores were indicative of greater self-perceived competence). Multilevel modeling suggested that on days when older adults reported higher internal locus of control, simple and complex reaction time was faster. Moreover, older adults, who typically demonstrated low levels of locus of control across the study, exhibited faster simple reaction times on those occasions when their internal locus of control was higher than their usual levels. Models with race as a moderator suggested that European Americans (EAs) experienced an increase in performance on the Digit Symbol Substitution Task (DSST) on occasions when their daily competence was high. A similar coupling relationship was not observed for AAs. In addition, EAs with low locus of control over the course of the study had faster complex reaction time when their daily locus of control was high. Discussion will focus on the possible mechanisms underlying the association between controls beliefs and cognition and differences in these coupling associated with race.